Intranasal Peptide-Based FpvA-KLH Conjugate Vaccine Protects Mice From Pseudomonas aeruginosa Acute Murine Pneumonia - Sen-Kilic, Emel; Blackwood, Catherine B.; Boehm, Dylan T.; Witt, William T.; Malkowski, Aaron C.; Bevere, Justin R.; Wong, Ting Y.; Hall, Jesse M.; Bradford, Shelby D.; Varney, Melinda E.; Damron, Fredrick Heath; Barbier, Mariette (Frontiers in Immunology, 2019)
Pseudomonas aeruginosa is an opportunistic pathogen causing acute and chronic respiratory infections associated with morbidity and mortality, especially in patients with cystic fibrosis. Vaccination against P. aeruginosa before colonization may be a solution against these infections and improve the quality of life of at-risk patients. To develop a vaccine against P. aeruginosa, we formulated a novel peptide-based P. aeruginosa subunit vaccine based on the extracellular regions of one of its major siderophore receptors, FpvA. We evaluated the effectiveness and immunogenicity of the FpvA peptides conjugated to keyhole limpet hemocyanin (KLH) with the adjuvant curdlan in a murine vaccination and challenge model. Immunization with the FpvA-KLH vaccine decreased the bacterial burden and lung edema after P. aeruginosa challenge. Vaccination with FpvA-KLH lead to antigen-specific IgG and IgM antibodies in sera, and IgA antibodies in lung supernatant. FpvA-KLH immunized mice had an increase in recruitment of CD11b+ dendritic cells as well as resident memory CD4+ T cells in the lungs compared to non-vaccinated challenged mice. Splenocytes isolated from vaccinated animals showed that the FpvA-KLH vaccine with the adjuvant curdlan induces antigen-specific IL-17 production and leads to a Th17 type of immune response. These results indicate that the intranasal FpvA-KLH conjugate vaccine can elicit both mucosal and systemic immune responses. These observations suggest that the intranasal peptide-based FpvA-KLH conjugate vaccine with curdlan is a potential vaccine candidate against P. aeruginosa pneumonia.